Prosedur Penyelesaian Perkara Wanprestasi Atas Perjanjian Pinjam Uang Yang Dilakukan Oleh Debitur Koperasi - I Komang Eka Adi Putra; I Nyoman Sukandia; I Wayan Kartika Jaya Utama (Warmadewa Press, 2024)
Cooperatives which regulate the movement of business fields in the formation of capital from the savings of its members regularly and continuously and can also be lent to its members in a practical, easy and fast way are called Savings and Loans Cooperatives for welfare purposes. That way the aim of establishing it is to make it easier for the community to make financial transactions easier, with the existence of a savings and loan cooperative that provides small interest but opportunities in capital can be cheap. With normative law implemented in the method used in this study, allowances from sources such as principles, principles, and legal literature are used in resolving cases of default on borrowing money in cooperatives. The results of this study are the results of evidence in court proceedings, evidence can be submitted by the plaintiff and the truth of the lawsuit and the defendant does not deny it. The proof of the case made the judge declare that it was legal to have defaulted on borrowing money within the scope of the cooperative.